«L'altro, il dialogo, lo specchio che ci rifrange» Carteggio Anceschi-Macrí (1941-1994) - Collini, Dario (Premio Ricerca «Città di Firenze», 2020)
This volume brings together 474 letters that Luciano Anceschi and Oreste Macrí wrote each other for 50 years. The strong point of the deep (and maybe unexpected) friendship between the two critics - based on the shared and fierce activism, on the common outlook of an «uncompromising humanism» - is curiously a dialectical progression that almost always excludes the perspective of a total agreement. It is a dialogue that springs from differences, and that exhorts to think about them. After the Second World War, the protagonists of the correspondence started to relaxedly discuss about the present and future of the European cultural civilization, the meaning of a literature that seems to illustrate a permanent state of crisis, and the events that gave life to the literary debate until the threshold of the new millennium, between post-hermetic tendencies and new experimentalisms.